2015
DOI: 10.1016/j.juro.2014.10.107
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Hospital Readmission Intensity after Radical Cystectomy

Abstract: Readmission intensity differs widely after discharge following radical cystectomy. As postoperative efforts to minimize the readmission burden increase, a better understanding of the factors that contribute to the highest intensity readmissions will help direct limited resources (eg telephone calls, office visits) toward high yield areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 24 publications
2
29
1
Order By: Relevance
“…Despite the lack of a difference, we highlight the fact that readmissions following cystectomy are high intensity stays as most readmitted patients had multiple new diagnoses at the time of readmission, and the readmission LOS was 5 days following open cystectomy and 4 days following RARC. 16 Emergency department use was substantial in both cohorts, with just under one quarter of patients seen within 30 days of discharge, but did not differ significantly by approach. Taken together, our findings demonstrate that the substantial burden of readmissions following cystectomy on patients, providers and hospital systems is not altered by whether someone has an open or robotic-assisted surgery.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Despite the lack of a difference, we highlight the fact that readmissions following cystectomy are high intensity stays as most readmitted patients had multiple new diagnoses at the time of readmission, and the readmission LOS was 5 days following open cystectomy and 4 days following RARC. 16 Emergency department use was substantial in both cohorts, with just under one quarter of patients seen within 30 days of discharge, but did not differ significantly by approach. Taken together, our findings demonstrate that the substantial burden of readmissions following cystectomy on patients, providers and hospital systems is not altered by whether someone has an open or robotic-assisted surgery.…”
Section: Discussionmentioning
confidence: 85%
“…In an administrative database analysis, James et al showed that 26% of cystectomy readmissions were considered modifiable 18 and Krishnan et al demonstrated that detection of at-risk patients could be improved with early clinician contact. 21 It is likely that even in the cases of some non-modifiable readmissions, earlier identification of at-risk patients would allow for prompt intervention and a reduction in the intensity of the overall readmission episode 16 as was evident by the multiple new diagnoses present in our cohort at the time of readmission.…”
Section: Discussionmentioning
confidence: 98%
“…Skolarus et al [23] used SEER-Medicare data and identified 1782 patients who underwent a radical cystectomy between 2003 and 2009 and found that 25.5 % of patients were readmitted within 30 days. After categorizing the readmissions by length-of-stay intensity defined as <3 days, 3-4 days, 5-7 days, and >7 days, they found no difference in length-of-stay intensity when stratified by age or by type of urinary diversion.…”
Section: Complicationsmentioning
confidence: 99%
“…One study using data from the Healthcare Cost and Utilization Project's State Impatient Database examined patients undergoing similarly high‐risk abdominal surgery (including open abdominal aortic aneurysm repair, cystectomy, esophagectomy, and pancreatectomy) and found that 19.4% of patients were discharged to a skilled nursing facility, which is similar to the rate of 22.8% found in this study. Another study looked at 30‐day readmission intensity in cystectomy patients using Surveillance, Epidemiology, and End Results‐Medicare data and found that 77% of readmissions occurred within the first week of discharge . This study, however, was limited to 30 days of follow‐up and therefore was not able to assess readmissions over the course of the year following surgery, as was done in our study.…”
Section: Discussionmentioning
confidence: 90%